Desenvolvimento de um índice de vulnerabilidade em saúde nos municípios do Ceará - Gerlânia Maria Rocha Sousa; Maria Elisa Zanella; Patrícia Verônica Pinheiro Sales Lima; João Luís Sampaio Olímpio; Marysol Dantas de Medeiros; Andréa Ferreira da Silva (Confins)
Health is very important for promoting sustainable development and reducing social vulnerability, and is largely determined by environmental, economic and social factors. The general aim of this article is to assess the health vulnerability of municipalities in Ceará by constructing the Health Vulnerability Index (HVI). The index was calculated using statistical multivariate analysis techniques, making it possible to hierarchize the municipalities of Ceará in terms of the vulnerability studied. To complement the study, the Global and Local Moran indices were also calculated, allowing us to visualize the spatial autocorrelation of the HVI in relation to the state's municipalities, verifying whether or not these localities are similar to their respective close neighbors. The results indicated that the majority of Ceará's municipalities fall into the most vulnerable health group and a minority belong to the intermediate and lowest HVI groups. The cities in the interior and furthest away from the capital are the ones with the highest rates, highlighting the reality present in many places in Brazil. The study also showed that the high HVI regime stood out among the state's cities, forming high-high agglomerations, which means that the high vulnerability in these locations is related to the high vulnerabilities of their neighbors.